Fair play - Sullivan, James A.; Ford, Paul, 1901-1976; Cinetel Films ([United States] : [publisher not identified], 1972)
In Fair Play, Texas, a boy goes to visit his uncle whose saloon-hotel is a haven for outlaws. Two con artists try to sell a fake Gatling gun to both his uncle and his hated enemy, Purvis. Eventually the hotel and saloon are blown up during a shootout between the two warring factions. --
Paul Ford, Robert Middleton, Terry Wilson, Paul Glaser, Barbara Hancock, Phillip Alford.
Cinematographer, Robert C. Jessup; editors, Jerry Caraway, Curtis Poe; music, Jack Carney.
In English or Spanish.
Online resource; title from opening/closing credits (Digitalia Film Library, viewed August 14, 2015).
Keywords: Outlaws -- Drama; Swindlers and swindling -- Drama; Western films; Western television programs; Internet videos; Streaming video